Symmetry problem - Ramm, Alexander G. (My University, 2012)
A novel approach to an old symmetry problem is developed. A new proof is given for the following symmetry problem, studied earlier: if Δu = 1 in D ⊂ R[superscript 3], u = 0 on S, the boundary of D, and u[subscript N] = const on S, then S is a sphere. It is assumed that S is a Lipschitz surface homeomorphic to a sphere. This result has been proved in different ways by various authors. Our proof is based on a simple new idea.
Keywords: Symmetry; Symmetry problems; Pompeiu problem